HUBUNGAN ASUPAN ENERGI, LEMAK, DAN AKTIVITAS FISIK DENGAN STATUS GIZI PADA MAHASISWA PROGRAM STUDI S-1 ILMU GIZI UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA - Fanessa Dea Pithaloka (2020)
Nutritional status is a condition caused by a balance between the intake of nutrients from food with the nutritional needs needed for the body's metabolism. Every individual needs different nutrient intake between individuals, this depends on the person's age, sex, body activity in a day, body weight, and others. This research is a cross sectional study of 45 respondents with stratified random sampling technique. The purpose of this study was to determine the relationship of energy intake, fat, and physical activity with nutritional status. Data was collected through online and google interview forms and maximum measurements one month ago. Chi-square test results showed no significant relationship between energy intake (p = 1,000), fat (0.482), and physical activity (p = 0.503) with nutritional status. The conclusion obtained in this study is that there is no significant relationship between energy intake, fat, physical activity and nutritional status.